If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 + -4x = 13 + -3x Solving -24 + -4x = 13 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -24 + -4x + 3x = 13 + -3x + 3x Combine like terms: -4x + 3x = -1x -24 + -1x = 13 + -3x + 3x Combine like terms: -3x + 3x = 0 -24 + -1x = 13 + 0 -24 + -1x = 13 Add '24' to each side of the equation. -24 + 24 + -1x = 13 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 13 + 24 -1x = 13 + 24 Combine like terms: 13 + 24 = 37 -1x = 37 Divide each side by '-1'. x = -37 Simplifying x = -37
| -9p-12=60 | | 3/4p=z-3.8 | | 6m-[2m+5]-4m= | | 2(3x-8)=x | | x-2*x+1/8-3/16 | | -2505/6-621/5 | | 2x/3+4/5=3x-5/4 | | 6v=-48 | | 91=7 | | t(t+3)=0 | | -8(n-3)=4(11n+6) | | -4(a+3)-2a=12 | | 3x^3-2x^2-6x+12=0 | | 0.2x-0.4=2 | | 3x-15y=-45 | | 5/9=k/19 | | 7x+6=331 | | (v+5)(v-8)=0 | | 1/6x+3(1/9x+4)=5 | | 3x^3-2x^3-6x+12=0 | | -4/17=18/m | | 6p(5p+5)=-8-2(p+12) | | 24-45x=16 | | 10+.75x=2.35 | | 2x+0=6 | | 3[4p-7]-[3x-7]= | | 4/5x+8=12 | | 19/a=17/9 | | 4(k-3)-7=6k-(5k-2) | | w+8=-8 | | 6/3-9 | | 6.4z-3=z+1.2 |